Histopathological and molecular evaluation of hydatid cysts according to necropsy findings of 52 equids in Türkiye - Celik, F.; Karabulut, B.; Uslug, M.; Cankaya, E.; Eroksuz, Y.; Simsek, S. (Cambridge Univ Press, 2025)
Echinococcus equinus is a parasitic cestode primarily maintained within an equine-canine life cycle, with horses, donkeys, mules, and other ungulates serving as intermediate hosts. Although E. equinus has historically been considered non-zoonotic, recent molecular studies suggest that this assumption may need to be reevaluated. This study aimed to investigate the presence and molecular characterization of E. equinus in equids from T & uuml;rkiye. A retrospective analysis of 52 equine necropsies performed between 2020 and 2025 identified hydatid cysts in one Arabian horse and two donkeys. Gross and histopathological examination confirmed the presence of hydatid cysts in the liver and lungs, exhibiting characteristic structural features. Molecular identification was conducted through PCR amplification targeting the mitochondrial cytochrome c oxidase subunit 1 (mt-CO1) gene, with all positive samples confirmed as E. equinus through sequence analysis. Phylogenetic analysis demonstrated a close relationship between the obtained sequences and reference E. equinus strains from other geographic regions. These findings provide the molecular confirmation of E. equinus in equids from T & uuml;rkiye and underscore the need for targeted surveillance to better understand its distribution, transmission, and zoonotic relevance, especially considering the first confirmed human case reported in the country in 2021.
Keywords: Echinococcus equinus; donkey; horse; mt-CO1 gene; histopathology